2007
DOI: 10.1007/s00420-007-0253-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement, evaluation, and assessment of peripheral neurological disorders caused by hand-transmitted vibration

Abstract: Regular exposure to hand-transmitted vibration can result in symptoms and signs of peripheral vascular, neurological and other disorders collectively known as the handarm vibration syndrome. The measurement of the effects of hand-transmitted vibration involves converting the evidence of disorder (symptoms and signs) into information that can be stored. Evaluation requires the use of scales on which to indicate the severity of the various symptoms and signs. Assessment involves a judgement of severity relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…The models with the smallest QIC values were also chosen as the best-fitting models for the relation between outcomes and vibration exposure. To aid comparison, a ΔQIC was calculated as the difference between the QIC value for a specific exposure model and the model including A (8) calculated with frequency weighting W h (ie, the ISO weighting method). By analogy, with the strength of evi- …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The models with the smallest QIC values were also chosen as the best-fitting models for the relation between outcomes and vibration exposure. To aid comparison, a ΔQIC was calculated as the difference between the QIC value for a specific exposure model and the model including A (8) calculated with frequency weighting W h (ie, the ISO weighting method). By analogy, with the strength of evi- …”
Section: Discussionmentioning
confidence: 99%
“…Case definition did not include subjects who reported temporary presence of tingling or numbness occurring while or after working with vibratory tools, during or following episodes of VWF or exposures to cold environment (8). The diagnosis of VWF was based on the findings of the medical interview assisted by color charts according to the criteria established by the Stockholm Workshop 1994 (5).…”
Section: Interview and Medical Investigationsmentioning
confidence: 99%
“…Therefore, changes in transmissibility reported in this study may not strictly be due to changes in frequency, since vibration exposure magnitude also increased when exposure frequency increased. Furthermore, several researchers have reported transmissibility increases with increasing magnitude [9,36,37]. Second, although participants' foot placement was controlled and all were given the same instruction with regard to how to stand, it could not be confirmed that all participants' maintained the same posture throughout the 45-second FTV exposure period.…”
Section: Limitations Of the Studymentioning
confidence: 95%
“…Raynaud's phenomenon of the feet has been examined mostly in conjunction with HAVS [7][8][9][10][11][12][13]. Given the similarities between the anatomy of the hands and feet it is not unreasonable to speculate that their resonant frequencies would be in the same range.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of numbness in the hand can be defined as an absence or loss of tactile sensation and may be associated with other symptoms like prickling or burning sensations, even though this may not be the only relevant definition. Patients can easily interpret symptoms differently or may have another definition for the symptom, which may confuse the picture of how common the HAVS is (23).…”
Section: Edlund Et Almentioning
confidence: 99%